Mangrove ecosystem Segmentation from Drone Images using Otsu Method - Pratiwi, Ni Made Dinda; Widiartha, I Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 3 (2021): JELIKU Volume 9 No 3, Februari 2021, 2021)
Mangrove ecosystems are found mainly in tropical and subtropical coastal areas. they are playing a very important ecological role in land-ocean interfaces. These ecosystems are protecting the environment and providing a habitat that supports many living organisms. Identification of area images in mangrove ecosystems is very helpful in monitoring and conservation of this ecosystem. In this study, we will present the segmentation of drone image taken from TAHURA Ngurah Rai mangrove area using otsu method. The otsu method giving well accuracy to segmented image to divide mangrove area and non mangrove area. Because Otsu method operates on a grayscale image so that it cannot distinguish the dark green of the tree canopies from the dark shadows of the trees, then the segmentation accuracy will decrease.